Palliative care needs and outcomes of patients with hepatocellular carcinoma: the case of Uganda cancer institute and Mulago national referral hospital - Nabachwa, Florence Nalutaaya (Department of Medicine, 2022)
Background: Hepatocellular carcinoma (HCC) is a leading cause of morbidity and mortality in Uganda. A previous qualitative study suggested multidimensional needs. It was important to ascertain these needs and the patients' outcomes. Aims / Objectives: To determine the Palliative Care needs and outcomes of patients with Hepatocellular Carcinoma enrolled on program at Uganda Cancer Institute (UCI) and Mulago National Referral Hospital (MNRH). Methods: A longitudinal, quantitative, descriptive study was conducted from eligible in patients using convenience sampling on those who had a clinical diagnosis of HCC and were aged >18. A structured questionnaire using validated tools was administered by face to face interview at baseline then by telephone follow up at 1, 2 and 3 months. These tools include socio-demographic disease information, APCA POS and symptom assessment. Ethics approval was granted by University of Cape Town and Uganda Cancer Institute. Results: Fifty participants were recruited and among these 68% < six months' duration of illness and 74% were male. All participants were identified as stage 3 or 4 disease with 72% having an ECOG performance status 0 – 2. Fourty two percent of participants received chemotherapy and out of these 18% completed the study. Seventy-two percent of participants scored moderate to severe pain (>3/5) with a Median of (IQR) 4(3 - 5) on APCA POS and for those completed the 90 days has a Mean of ± SD 0.7±1.2. Only 34% accessed morphine and 36% accessed a specialist in PC at baseline and none at a 90 day accessed a PC specialist. Abdominal fullness and early satiety were among the common symptoms at baseline and scored in 70% of participants. At the baseline 66% expected cure, with information obtained during the study their perceptions changed. The degree of understanding of the illness at baseline scored 22%, not understanding at all was 34% hence the majority 78% at 90 days had a full understanding of the disease. While 28% felt hopeless at baseline this improved on subsequent follow-ups. Insufficient spiritual support was more marked at 90 days scored in 56% of the participants. The study showed high attrition rates >50% at 1 month) as mainly due to high mortality. Conclusions: The majority of patients were young men presenting with a late stage disease and from rural areas with significant financial constraints. There are significant unmet needs including pain, heightened existential distress and lack of clear information or goal setting which require further strengthening of PC within the medical and oncology services.